Zirconium tin niobate calcium lead ceramic and preparation method and application thereof

By introducing high contents of Ca2+ and Nb5+ into antiferroelectric materials, adjusting the zirconium-ton ratio, and adopting a specific preparation process, the problem of difficult observation of phase change of antiferroelectric materials at room temperature and low energy storage density is solved, and the problem of low phase change of antiferroelectric materials is achieved. Highly efficient energy storage density and high efficiency dielectric ceramic materials.

CN119263820APending Publication Date: 2025-01-07GUANGDONG UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411210476.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing antiferroelectric materials are difficult to observe the phase change driven by electric field at room temperature, and the energy storage density is low, so they cannot be directly used to manufacture high-efficiency energy storage capacitors.

Method used

By introducing high contents of Ca2+ and Nb5+, the zirconium-ton ratio was adjusted, and the traditional solid-phase reaction method, casting and secondary sintering method was used to prepare (Pb0.93Ca0.07) (Zr0.975-xSnx)Nb0.02O3 ceramics were optimized to optimize their Energy storage performance.

Benefits of technology

It achieves high effective energy storage density and high energy storage efficiency. Ceramics show excellent performance in dielectric energy storage capacitors, with high breakdown electric field strength and stable dielectric properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263820A_ABST
    Figure CN119263820A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of dielectric materials, and discloses zirconium tin niobate calcium lead ceramic as well as a preparation method and application thereof. The molecular formula of the zirconium tin lead calcium niobate ceramic is (Pb < 0.93 > Ca < 0.07 >) (Zr < 0.975-x > Sn < x >) Nb < 0.02 > O < 3 >, wherein x is equal to 0.3 to 0.45. According to the preparation method, a traditional solid-phase reaction method, a tape casting process and a two-step sintering method are utilized, high-content Ca < 2 + > and Nb < 5 + > are introduced on the basis of PZ antiferroelectric ceramic, and the energy storage performance of the zirconium tin calcium lead niobate ceramic is explored by adjusting different zirconium tin ratios. When x is equal to 0.4, the (Pb0. 93Ca0. 07) (Zr0. 575Sn0. 4) Nb0. 02O3 ceramic has high effective energy storage density (Wre is equal to 14.60 J / cm < 3 >) and high energy storage efficiency (eta is equal to 85.58%), and can be applied to a dielectric energy storage capacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of dielectric materials, and in particular, relates to a calcium lead zirconium tin niobate ceramic and a preparation method and application thereof. Background Art

[0002] In recent years, pulse power technology has developed rapidly, and electronic components and products are developing towards miniaturization, integration and multifunctionality. Energy storage materials have attracted widespread attention. Adequate energy has become a prerequisite for ensuring social life and production. Although dielectric capacitors have extremely high power density, their energy storage density is low. Therefore, improving the energy storage density of dielectric capacitors has become a key public relations topic for scientific research institutions at home and abroad. Antiferroelectric (AFE) materials have higher energy density than ferroelectric (FE) materials and linear dielectrics due to their unique antiferroelectric-ferroelectric phase transition characteristics. They are considered to be one of the most suitable dielectric materials for high energy storage density capacitors. Adjacent dipoles in antiferroelectric materials are arranged in reverse parallel and have opposite polarization directions. Under the action of an external high electric field, the polarization direction of the dipoles reverses and tends to be consistent with the external field, inducing ferroelectrics and causing a sudden change in polarization intensity. At this time, the transmission energy is converted into dielectric energy and stored in the material. As the electric field strength gradually decreases, the ferroelectric phase disappears and returns to the initial antiferroelectric phase, at which time the dielectric energy is converted into transmission energy and released. And its residual polarization intensity is almost zero, which makes antiferroelectrics have a higher storage energy density. Lead zirconate (PbZrO3) is the first antiferroelectric compound discovered. Later, antiferroelectricity was also observed in other perovskite compounds. For example, PbHfO3, AgNO3, etc. Compared with ferroelectric materials, their residual polarizability is almost zero. Compared with linear dielectrics, their dielectric constants are much higher.

[0003] There are many types of antiferroelectric materials that have been discovered, which can be roughly divided into perovskite type, pyrochlore type, and liquid crystal type. Pure PbZrO3 is a typical ABO3 perovskite structure with high structural stability. It is the most studied antiferroelectric. At room temperature, pure lead zirconate is broken down before reaching the phase transition electric field, and it is difficult to observe the AFE-FE phase transition driven by the electric field. The unique phase transition characteristics of the AFE material have not yet been demonstrated, and it is not suitable for direct use in the manufacture of energy storage capacitors. Therefore, researchers often adjust the phase change behavior and optimize related properties through chemical modification to meet the requirements of the dielectric material as a pulse capacitor. By doping La 3+ , Ca 2+ , Nb 5+ Sn 4+ 、Ti 4+Through chemical modification by plasma, many different composition systems have been developed, such as PLZT ((Pb, La) (Zr, Ti) O3), PLZST ((Pb, La) (Zr, Sn, Ti) O3), PLZS ((Pb, La) (Zr, Sn) O3), PNZST (Pb (Nb (Zr, Sn, Ti)) O3), etc. These systems with reasonable chemical modification and good sintering methods can obtain high energy storage ceramics. Summary of the invention

[0004] The present invention is aimed at the problems existing in the prior art. The primary purpose is to provide a zirconium tin calcium lead niobate ceramic. The composition of the ceramic is (Pb 0.93 Ca 0.07 )(Zr 0.975-x Sn x )Nb 0.02 O3(PCZSN,x=0.3~0.45).

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned zirconium tin lead niobate calcium ceramics. The method prepares zirconium tin lead niobate calcium ceramics by a traditional solid phase reaction method, a tape casting process and a secondary sintering method.

[0006] Another object of the present invention is to provide an application of the above-mentioned calcium lead zirconium tin niobate ceramic.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] The molecular formula of a zirconium tin calcium lead niobate ceramic is (Pb 0.93 Ca 0.07 )(Zr 0.975-x Sn x )Nb 0.02 O3,x=0.3~0.45.

[0009] The preparation method of the calcium lead zirconium tin niobate ceramic comprises the following steps:

[0010] S1. PbO, CaCO3, ZrO2, SnO2, Nb2O5 and excess 3 to 5 wt% PbO were wet-milled in a conventional planetary ball mill, and ethanol and a milling medium were added to obtain a slurry;

[0011] S2. The slurry is dried at 90 to 120 ° C, sieved after grinding, and then pre-fired at 850 to 950 ° C to obtain a ceramic powder;

[0012] S3. The ceramic powder is ball-milled, dried and sieved in steps S1 and S2, and the obtained powder is rolled with octylphenol polyoxyethylene ether and a solvent to obtain a premixed slurry; polyvinyl butyral, a solvent and trioctyl trimellitate are then added and rolled to obtain a casting slurry with a viscosity of 600 to 800 mPa·s.

[0013] S4. Place the cast slurry in a mold, with a substrate film belt speed of 0.12-0.16 m / min, a drying temperature of 35-45°C, and a holding time of 15-20 min; then debind at 300-600°C, and finally sinter at 1100-1200°C to obtain calcium zirconium tin lead niobate ceramics, abbreviated as PCZSN.

[0014] Preferably, the ball milling media in step S1 are zirconium dioxide balls with a diameter of 2 to 3 mm and zirconium dioxide balls with a diameter of 4 to 5 mm in a mass ratio of 1:1.

[0015] Preferably, the ball milling speed in step S1 is 250-300 rpm, and the ball milling time is 18-24 h.

[0016] Preferably, the drying time in step S2 is 5 to 10 hours, the sieving mesh size is 40 to 80 meshes, and the pre-burning time is 2 to 3 hours.

[0017] Preferably, the solvents in step S3 are anhydrous ethanol and butanone in a mass ratio of 1:1.

[0018] Preferably, the mass ratio of the powder, octylphenol polyoxyethylene ether, solvent, polyvinyl butyral and trioctyl trimellitate in step S3 is (45-50):(0.8-0.9):(58-60):(5.3-5.5):(1.8-2).

[0019] The method for preparing calcium lead zirconium tin niobate ceramics according to claim 2 is characterized in that the rotation speed of the rolling mill in step S3 is 100-200 rpm, and the rolling milling time is 18-24 hours.

[0020] The application of the zirconium tin calcium lead niobate ceramic in the field of dielectric energy storage capacitors.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The ceramic obtained by the ternary phase diagram design of the system is (Pb 0.93 Ca 0.07 )(Zr 0.975-x Sn x )Nb 0.02 O3 (PCZSN, x = 0.3 ~ 0.45), based on PZ antiferroelectric ceramics, introduces high content Ca2+ (7 mol%) and Nb 5+ The energy storage performance of PCZSN ceramics was investigated by adjusting different zirconium-tin ratios. 0.93 Ca 0.07 )(Zr 0.575 Sn 0.4 )Nb 0.02 O3 ceramics have a high effective energy storage density (W rec =14.60J / cm 3 ) and high energy storage efficiency (η=85.58%), and can be applied in dielectric energy storage capacitors.

[0023] 2. The present invention uses a traditional solid phase reaction method, a tape casting process and a two-step sintering method to prepare calcium lead zirconium tin niobate ceramics. The method uses a traditional solid phase reaction to obtain a PCZSN ceramic powder with high purity without subsequent treatment. The tape casting process can obtain a small, flat and uniform ceramic body, and the two-step sintering method can obtain a small and uniform microstructure, which is beneficial to improve the breakdown electric field strength of PCZSN thick film ceramics, thereby improving the energy storage performance of PCZSN ceramics. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The room temperature X-ray diffraction patterns and local magnified patterns of the PCZSN thick film ceramics prepared in Examples 1-4.

[0025] Figure 2 The scanning electron microscope (SEM) images of the PCZSN thick film ceramics prepared in Examples 1-4;

[0026] Figure 3 The dielectric constant and dielectric loss of the PCZSN thick film ceramics prepared in Examples 1-4 vary with temperature;

[0027] Figure 4 The dielectric constant and dielectric loss of the PCZSN thick film ceramics prepared in Examples 1-4 vary with temperature at a test frequency of 5 kHz.

[0028] Figure 5 PE hysteresis loop and IE curve measured for the PCZSN thick film ceramics prepared in Examples 1-4;

[0029] Figure 6 The effective energy storage density and energy storage efficiency of the PCZSN thick film ceramics prepared in Examples 1-4 under the action of an electric field.

[0030] Figure 7 The effective energy storage density W of the hysteresis loop of the PCZSN thick film ceramics prepared in Examples 1-4 is rec . DETAILED DESCRIPTION

[0031] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0032] In the embodiments of the present invention, PbO, CaCO3, ZrO2, SnO2, and Nb2O5 (all purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) were used for crystal structure analysis in material structure characterization and performance testing using a DMAX-UltimaIV X-ray diffractometer (XRD) from Rigaku Corporation of Japan. Hitachi S-3400 (II) scanning electron microscope (SEM) was used for surface morphology analysis. Dielectric properties were measured using an Agilent E49840A precision impedance analyzer from Agilent Technologies, Inc., USA. Ferroelectric properties were measured using a Multiferroic ferroelectric integrated test system from Radiant, Inc., USA.

[0033] Example 1

[0034] 1. PbO, CaCO3, ZrO2, SnO2, and Nb2O5 were weighed and placed in a 250 mL nylon ball mill according to the stoichiometric ratio and the purity of the chemicals, and then an excess of 3 wt% PbO was added to compensate for the volatilization of Pb during high temperature sintering;

[0035] 2. Use a common planetary ball mill for wet ball milling, add an appropriate amount of alcohol, the ball milling medium is zirconium dioxide balls (diameters of 3 mm and 5 mm) with a mass ratio of 1:1, the speed is set at 250 rpm, and the ball milling time is 24 h to obtain a slurry;

[0036] 3. The slurry was placed in an oven and dried at 120°C for 5 hours, ground in an agate mortar, passed through 40-mesh and 80-mesh sieves in sequence, and then pre-calcined at 920°C for 2 hours to obtain ceramic powder;

[0037] 4. The ceramic powder is ball-milled and dried and sieved according to steps 2 and 3. The obtained ceramic powder (about 50 g) is placed in a rolling mill, 0.9 g of a dispersant (octylphenol polyoxyethylene ether) and 40 g of a solvent (anhydrous ethanol and butanone in a mass ratio of 1:1) are added, and then rolling is performed at a speed of 200 rpm for more than 24 hours to obtain a premixed slurry; 1.5 g of a binder (polyvinyl butyral) is added and rolling is performed at a speed of 200 rpm for more than 18 hours; then 18 g of a solvent (anhydrous ethanol and butanone in a mass ratio of 1:1), 4 g of a binder (polyvinyl butyral) and 2 g of a plasticizer (trioctyl trimellitate) are added and ball-milled at a speed of 200 rpm for more than 24 hours to obtain a uniformly mixed casting slurry with a viscosity of 600 to 800 mPa·s.

[0038] 5. The cast slurry was placed in a mold, the substrate film belt speed was set to 0.16 m / min, the drying temperature was 45 ° C, and the holding time was 20 min; the binder was removed at 300 ° C for 0.5 h, the binder was removed at 600 ° C for 7 h, and finally sintered at 1160 ° C for 4 h to obtain zirconium tin calcium lead niobate thick film ceramics, whose molecular formula is (Pb 0.93 Ca 0.07 )(Zr 0.975-x Sn x )Nb 0.02 O3 (x=0.3), abbreviated as PCZSN4, has a thickness of 15 to 40 μm.

[0039] Example 2

[0040] The difference from Example 1 is that the molecular formula of the zirconium tin calcium lead niobate thick film ceramic is (Pb 0.93 Ca 0.07 )(Zr 0.975- x Sn x )Nb 0.02 O3 (x=0.35), abbreviated as PCZSN3, has a thickness of 15 to 40 μm.

[0041] Example 3

[0042] The difference from Example 1 is that the molecular formula of the zirconium tin calcium lead niobate thick film ceramic is (Pb 0.93 Ca 0.07 )(Zr 0.975- x Sn x )Nb 0.02 O3 (x=0.4), abbreviated as PCZSN2, has a thickness of 15 to 40 μm.

[0043] Example 4

[0044] The difference from Example 1 is that the molecular formula of the zirconium tin calcium lead niobate thick film ceramic is (Pb 0.93 Ca 0.07 )(Zr 0.975- x Sn x )Nb 0.02 O3 (x=0.45), abbreviated as PCZSN1, has a thickness of 15 to 40 μm.

[0045] Figure 1 The room temperature X-ray diffraction patterns and local magnified patterns of the PCZSN thick film ceramics prepared in Examples 1-4 are shown. Figure 1It can be seen that the characteristic peaks of the test spectrum are consistent with the diffraction peaks of the standard JCPDS card. The diffraction peaks are sharp and free of impurity peaks, indicating that PCZNS ceramics with different zirconium-tin ratios are all perovskite phase structures. In the local magnified image of 43.45-44.95°, it can be observed that the diffraction peaks are separated into two peaks, (200) and (002). With the increase of the zirconium-tin ratio, the separation of the (200) and (002) diffraction characteristic peaks gradually becomes obvious, and shifts to a lower angle, indicating that the interplanar spacing between (200) and (002) increases, thereby expanding the unit cell volume. According to the Bragg diffraction formula 2dsinθ=nλ (d is the interplanar spacing, θ is the diffraction angle, and λ is the test wavelength), when the zirconium-tin ratio increases, Zr 4+ Enter the lattice to replace Sn 4+ , and Zr 4+ The ionic radius Greater than Sn 4+ The ionic radius The interplanar spacing (d) will become larger.

[0046] Figure 2 The following are scanning electron microscope (SEM) images of PCZSN thick film ceramics prepared in Examples 1-4. Among them, (a) is PCZSN1, (b) is PCZSN2, (c) is PCZSN3, and (d) is PCZSN4. Figure 2 It can be seen that the grain morphology of all ceramics is hexagonal, with a small number of spherical small grains distributed at the junction of large grains, clear grain boundaries, no pores and other impurities, and highly dense microstructure. The grain size distribution data analyzed based on ImageJ software is reflected in the corresponding distribution histogram. With the increase of zirconium-tin ratio, the average grain of PCZSN4 in Example 1 is 2.70μm and increases to the average grain of PCZSN1 in Example 4 is 2.95μm. The dense microstructure shows that it is an antiferroelectric ceramic with a high breakdown electric field strength, thereby improving the energy storage density.

[0047] Figure 3 The dielectric constant and dielectric loss of the PCZSN thick film ceramics prepared in Examples 1-4 vary with temperature, where the test voltage is 1V and the test frequencies are 1kHz, 5kHz, 10kHz, 50kHz, and 100kHz, respectively. (a) is PCZSN1, (b) is PCZSN2, (c) is PCZSN3, and (d) is PCZSN4. Figure 3It can be seen that the ceramic component has good stability within 1 to 100kHz, and the dielectric loss is always kept within 3%. PCZSN1, PCZSN2 and PCZSN3 with low zirconium-tin ratios undergo phase transitions from antiferroelectric (AFE) to multicellular paraelectric phase (MCC) to cubic paraelectric phase (P) as the temperature increases. However, the PCZSN4 ceramic component with high zirconium-tin ratio only undergoes phase transitions from antiferroelectric (AFE) to cubic paraelectric phase (P) as the temperature increases. This is due to the high Sn content. 4+ The random distribution of ion concentration leads to the inhomogeneous structure of the multicellular paraelectric (MCC) phase. The Curie peaks of all ceramics are relatively broad dielectric constant peaks, rather than the traditional sharp dielectric peaks. As the temperature changes, PCZSN thick film ceramics undergo AFE-PE MCC -PE C Phase change process. And with the increase of zirconium-tin ratio, AFE phase to PE MCC The phase transition temperature increases and the relative dielectric constant also increases, indicating that the stability of the PCZSNAFE phase is enhanced. MCC The existence of is beneficial to refine the PE hysteresis loop, thereby improving the η of AFE. Figure 4 The dielectric constant and dielectric loss of the PCZSN thick film ceramics prepared in Examples 1-4 vary with temperature at a test frequency of 5 kHz. Figure 4 It can be seen that at room temperature with a frequency of 5 kHz, the relative dielectric constant of PCZSN ceramics increases with the increase of the zirconium-tin ratio. Due to their dense microstructure, the dielectric loss of PCZSN thick film ceramics with different zirconium-tin ratios is always kept within 3%.

[0048] Figure 5 PE hysteresis loops and IE curves of PCZSN thick film ceramics obtained in Examples 1-4, where (a) is PCZSN1, (b) is PCZSN2, (c) is PCZSN3, and (d) is PCZSN4. Figure 5 It can be seen that the electric field value corresponding to the maximum current in the IE curve and the maximum slope change of the PE curve is the antiferroelectric-ferroelectric phase transition electric field of the material. The appearance of the wide current peak corresponds to the relaxivity caused by the uneven distribution of Sn4+. With the increase of the zirconium-tin ratio, the current gap width gradually narrows, the PE hysteresis loop becomes thicker, and the current peak shifts to the high electric field. The final formation of the current spike indicates the continuous weakening of the relaxivity and the enhancement of the AFE. With the increase of the zirconium-tin ratio, the phase transition electric field of the ceramic changes differently. Its antiferroelectric-ferroelectric phase transition electric field (E AFE-FE ) first increased from 252 kV / cm to 339 kV / cm and then decreased to 244 kV / cm; the ferroelectric-antiferroelectric phase transition electric field (E FE-AFE ) gradually decreased from 231 kV / cm to 117 kV / cm; the hysteresis electric field (ΔE, EAFE-FE -E FE-AFE ) dropped from 21kV / cm to 128kV / cm. PCZSN4 undergoes multi-level phase transition under the action of electric field, which makes the polarization intensity of PCZSN4 ceramic component greater than that of other components, and also increases the hysteresis field width of PCZSN4 ceramic, resulting in reduced energy storage efficiency.

[0049] Figure 6 The effective energy storage density and energy storage efficiency of the PCZSN thick film ceramics prepared in Examples 1-4 under the action of an electric field. Among them, (a) is PCZSN1, (b) is PCZSN2, (c) is PCZSN3, and (d) is PCZSN4. Figure 6 It can be seen that the effective energy storage density of all ceramics increases with the increase of electric field. When the electric field increases to the antiferroelectric-ferroelectric transition field, the polarization intensity rises rapidly, causing the effective energy storage density to increase sharply. Figure 7 The effective energy storage density W of the hysteresis loop of the PCZSN ceramics prepared in Examples 1-4 is rec ,Depend on Figure 7 It can be seen that the energy storage efficiency of PCZSN ceramics gradually decreases with the increase of Zr / Sn ratio. The PE loop of PCZSN1 ceramics is slender and shows typical relaxation, which is due to the high Sn 4+ The content of AFE causes the macroscopic AFE domain to split into smaller polar nano-regions, which maintain a small P after external electric field stimulation. r Finally, the energy storage efficiency of PCZSN1 ceramics remained above 93.7%. The relaxivity of PCZSN2 and PCZSN3 weakened but still maintained. With the increase of the external electric field, the energy storage efficiency first decreased and then increased. Near the switching electric field, the η of PCZSN2 and PCZSN3 had minimum values ​​of 78% and 65%, respectively. Due to the occurrence of MPT and Zr 4+ Polarizability is greater than Sn 4+ , PCZSN has a large P max So it has the maximum energy storage density W tot , but also has the largest P r and ΔE show lower η and W rec Among them, PCZSN1 has a higher energy storage efficiency (η>90%), and PCZSN2 has the largest effective energy storage density (W rec =14.60J / cm 3 ), while having an energy storage efficiency of 85.58%.

[0050] The present invention adopts the traditional solid phase reaction method to synthesize PCZSN ceramic powders with different zirconium-tin ratios, and uses the tape casting process to obtain PCZSN ceramic thick film green bodies. According to X-ray diffraction (XRD), all components are determined to be pure perovskite structures, and scanning electron microscopy (SEM) observes that the sample sintering grain distribution and size are uniform and dense, and the grain size is 2.70-2.95μm. The electrical properties of the ceramic used have a dielectric loss of less than 3% in the low temperature range, and the ceramic has good stability in the 1-100kHz frequency range. Sn 4+ Doping PZ ceramics can refine the ceramic grains to optimize the hysteresis loop, thereby increasing the effective energy storage density. Excessive Sn content will also reduce the polarization strength. According to the antiferroelectric tolerance factor formula, Ca 2+ Doping is beneficial to improve the stability of the antiferroelectric phase of PZS[Pb(Zr,Sn)O3] ceramics, thereby increasing the phase transition electric field, but it will also increase the hysteresis. 4+ and Ca 2+ Although the PCZS ceramics obtained by doping have a high energy storage efficiency, the effective energy storage density is not high. The present invention introduces a high content of Ca on the basis of PZ antiferroelectric ceramics. 2+ (7 mol%) and Nb 5+ By adjusting different zirconium-tin ratios to explore the energy storage performance of PCZSN ceramics, when x = 0.4, (Pb 0.93 Ca 0.07 )(Zr 0.575 Sn 0.4 )Nb 0.02 O3 ceramics have a high effective energy storage density (W rec =14.60J / cm 3 ) and high energy storage efficiency (η=85.58%), and can be applied in dielectric energy storage capacitors.

[0051] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A zirconium tin calcium lead niobate ceramic, characterized in that: The molecular formula of the zirconium tin calcium lead niobate ceramic is (Pb 0.93 Ca 0.07 )(Zr 0.975-x Sn x )Nb 0.02 O3,x=0.3~0.

45.

2. The method for preparing calcium lead zirconium tin niobate ceramic according to claim 1, characterized in that: The steps include: S1. PbO, CaCO3, ZrO2, SnO2, Nb2O5 and excess 3 to 5 wt% PbO were wet-milled in a conventional planetary ball mill, and ethanol and a milling medium were added to obtain a slurry; S2. The slurry is dried at 90 to 120°C, sieved after grinding, and then pre-fired at 850 to 950°C to obtain a ceramic powder; S3. The ceramic powder is ball-milled, dried and sieved in steps S1 and S2, and the obtained powder is rolled with octylphenol polyoxyethylene ether and a solvent to obtain a premixed slurry; polyvinyl butyral, a solvent and trioctyl trimellitate are then added and rolled to obtain a casting slurry with a viscosity of 600 to 800 mPa·s. S4. Place the cast slurry in a mold, with a substrate film belt speed of 0.12-0.16 m / min, a drying temperature of 35-45°C, and a holding time of 15-20 min; then debind at 300-600°C, and finally sinter at 1100-1200°C to obtain calcium zirconium tin lead niobate ceramics, abbreviated as PCZSN.

3. The method for preparing calcium lead zirconium tin niobate ceramics according to claim 2, characterized in that: The ball milling media in step S1 are zirconium dioxide balls with a diameter of 2 to 3 mm and zirconium dioxide balls with a diameter of 4 to 5 mm in a mass ratio of 1:

1.

4. The method for preparing calcium lead zirconium tin niobate ceramics according to claim 2, characterized in that: The ball milling speed in step S1 is 250-300 rpm, and the ball milling time is 18-24 hours.

5. The method for preparing calcium lead zirconium tin niobate ceramics according to claim 2, characterized in that: The drying time in step S2 is 5 to 10 hours, the sieving mesh size is 40 to 80 meshes, and the pre-burning time is 2 to 3 hours.

6. The method for preparing calcium lead zirconium tin niobate ceramics according to claim 2, characterized in that: The solvents in step S3 are anhydrous ethanol and butanone in a mass ratio of 1:

1.

7. The method for preparing calcium lead zirconium tin niobate ceramics according to claim 2, characterized in that: The mass ratio of the powder, octylphenol polyoxyethylene ether, solvent, polyvinyl butyral and trioctyl trimellitate in step S3 is (45-50):(0.8-0.9):(58-60):(5.3-5.5):(1.8-2).

8. The method for preparing calcium lead zirconium tin niobate ceramics according to claim 2, characterized in that: The rotation speed of the rolling mill in step S3 is 100-200 rpm, and the rolling milling time is 18-24 hours.

9. Application of the calcium lead zirconium tin niobate ceramic according to claim 1 in the field of dielectric energy storage capacitors.

Citation Information

Patent Citations

  • High-energy-storage lead zirconate-based antiferroelectric multilayer ceramic capacitor and preparation method thereof

    CN111574198A

  • Zirconium titanium tin lead niobate thick film ceramic and preparation method and application thereof

    CN112209711A

  • Lead calcium zirconate stannate ceramic as well as preparation method and application thereof

    CN117602930A